DRUG UTILIZATION STUDY IN THE PATIENTS OF MYOCARDIAL INFARCTION AT A TERTIARY CARE HOSPITAL - DHAKA, AMIT KUMAR; PANCHOLI, DEVANG; MEENA, VIMLESH KUMAR; SAINI, GAURAV; JAIN, ARCHANA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the pattern of drug utilization, demographic characteristics, routes of administration, duration of hospital stay, and clinical outcomes in patients with myocardial infarction admitted to a tertiary care hospital. Methods: This was a hospital-based observational study conducted over a period of six months in the Pharmacology Department in coordination with the Cardiology Department of a tertiary care hospital in southern Rajasthan. A total of 100 patients with confirmed diagnosis of myocardial infarction were included. Data regarding demographics, drug prescriptions from admission to discharge, routes of administration, fixed-dose combinations, and clinical outcomes were collected from inpatient records and analysed descriptively. Results: The majority of patients were aged 61–70 y (37%), followed by 51–60 y (32%), with a marked male predominance (82%). Most patients recovered (93%), while in-hospital mortality was 7%. Combination routes of drug administration (oral, sublingual, and parenteral) were used in 84% of patients. Half of the patients had a hospital stay of 3–4 d. Antiplatelet drugs were prescribed to 99% of patients, with dual antiplatelet therapy being most common (73%). Statins (94%), beta-blockers (88%), anticoagulants (85%), and nitrates (89%) were widely used. Proton pump inhibitors were prescribed to all patients, while antibiotics were used in 51%. Fixed-dose combinations, particularly aspirin with clopidogrel and statins, were frequently prescribed. Conclusion: The study demonstrates a high level of adherence to evidence-based guidelines in the pharmacological management of myocardial infarction at the tertiary care hospital. The prescribing pattern reflects rational use of essential cardiovascular drugs and effective acute management, as evidenced by favourable clinical outcomes. However, the use of certain non-cardiac medications highlights the need for regular prescription audits to further promote rational drug use.